An Updated Indirect Comparison of Elranatamab Versus a Real-World External Control Arm in Triple-Class Refractory Multiple Myeloma - Costa LJ; LeBlanc TW; Tesch H; Sonneveld P; Johnson SM; Vekeman F; Hlavacek P; Meche A; Kim CH; Cislo P; Hughes DM; Nador G; et al. (Blood and Lymphatic Cancer: Targets and Therapy, 2025)
Luciano J Costa,1 Thomas W LeBlanc,2 Hans Tesch,3 Pieter Sonneveld,4 Sarasa MA Johnson,5 Francis Vekeman,5 Patrick Hlavacek,6 Aster Meche,6 Chai Hyun Kim,6 Paul Cislo,7 David M Hughes,8 Guido Nador,9 Marco DiBonaventura6 1University of Alabama at Birmingham, Birmingham, AL, USA; 2Duke University School of Medicine, Durham, NC, USA; 3Bethanien Hospital, Frankfurt, Germany; 4Department of Hematology, Erasmus MC Cancer Institute, Rotterdam, the Netherlands; 5STATLOG Inc, Montreal, QC, Canada; 6Chief Medical Affairs Office, Pfizer Inc, New York, NY, USA; 7Global Biometrics and Data Management, Pfizer Inc, Groton, CT, USA; 8Oncology Medical Affairs, Pfizer Inc, Cambridge, MA, USA; 9Oncology Medical Affairs, Pfizer Ltd, Surrey, UKCorrespondence: Marco DiBonaventura, Pfizer Inc, 66 Hudson Boulevard East, 15th Floor, New York, NY, 10001, USA, Tel +1 929 237 0451, Email marco.dibonaventura@pfizer.comPurpose: Elranatamab is a BCMAxCD3 bispecific antibody approved for the treatment of relapsed/refractory multiple myeloma (RRMM). The registrational Phase 2 MagnetisMM-3 (NCT04649359) trial was single-armed; the aim of this indirect comparison was to contextualize the efficacy of the most recent 28.4-month follow-up data cut from this trial, allowing for more mature data, with real-world data serving as an external control.Patients and Methods: We conducted a retrospective cohort study to indirectly compare the efficacy observed in the elranatamab arm of MagnetisMM-3 Cohort A (BCMA-naïve; N=123) from the March 26, 2024 data cut with COTA, a US-based oncology electronic health record database, as an external control. All MM patients with triple-class refractory disease who initiated a new line of therapy (representing real-world physician’s choice) between November 2015 and August 2023 in the COTA database were included. MagnetisMM-3 inclusion (eg, ≥ 18 years, measurable disease within 90 days of the index, Eastern Cooperative Oncology Group [ECOG] ≤ 2) and exclusion criteria (eg, plasma cell leukemia, smoldering MM) were applied to obtain comparable patient populations across sources. The elranatamab cohort was compared with the physician’s choice cohort on progression-free survival (PFS), overall survival (OS), and duration of response (DOR) using Cox proportional hazard models implementing inverse probability of treatment weighting to adjust for any remaining imbalances on confounding variables.Results: N=123 patients treated with elranatamab were compared with 577 patients treated with real-world physicians’ choice of therapy. Compared with physician’s choice, elranatamab significantly improved PFS (HR = 0.38 [0.22, 0.65], p< 0.05), OS (HR = 0.58 [0.35, 0.96], p< 0.05), and DOR (HR = 0.16 [0.07, 0.34], p< 0.05).Conclusion: In this comparison of patients from the MagnetisMM-3 trial and real-world patients who resemble those from the trial, patients treated with elranatamab exhibited significantly better clinical outcomes compared with treatments currently used in real-world clinical practice.Keywords: hematology, bispecific antibody, efficacy, clinical trial, electronic health record